2020
DOI: 10.1111/gwao.12497
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐earner parent couples’ work and care during COVID‐19

Abstract: COVID‐19 and the associated lockdowns meant many working parents were faced with doing paid work and family care at home simultaneously. To investigate how they managed, this paper draws a subsample of parents in dual earner couples (n=1,536) from a national survey of 2,722 Australian men and women conducted during lockdown in May 2020. It asked how much time respondents spent in paid and unpaid labour, including both active and supervisory care, and about their satisfaction with work‐family balance and how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
447
4
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 423 publications
(514 citation statements)
references
References 18 publications
44
447
4
19
Order By: Relevance
“…Families may rally around parents in frontline jobs and such parents may especially value family support and their relationships with children as they face the daily realities of the pandemic at work. Thus, although such care providers clearly have experienced signi cant stress and demands in their work that impact them in other ways (Craig & Churchill, 2020), for some these experiences may bring their family closer or at least protect against pandemic-related decrements in family functioning during this time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Families may rally around parents in frontline jobs and such parents may especially value family support and their relationships with children as they face the daily realities of the pandemic at work. Thus, although such care providers clearly have experienced signi cant stress and demands in their work that impact them in other ways (Craig & Churchill, 2020), for some these experiences may bring their family closer or at least protect against pandemic-related decrements in family functioning during this time.…”
Section: Discussionmentioning
confidence: 99%
“…As one key example of a broad pandemic stressor, families around the world report being affected by quarantine and mandatory social distancing (Brooks et al, 2020). These quarantine practices result in challenges to work-family balance through less support for parents from employers and spouses Craig & Churchill, 2020), unemployment (Brown et al, 2020), online schooling demands (Segre et al, 2020), and increased caregiver burden (Russell et al, 2020;Patrick et al, 2020). Although quarantine may entail spending more time at home with family, Ammar et al (2020) found that family members in Asia, Africa, and Europe reported feeling more socially isolated as a result of fewer opportunities to visit with family outside of the home as well as friends and neighbors during quarantine.…”
Section: Pandemic Life Events As Family Stressorsmentioning
confidence: 99%
See 3 more Smart Citations